Antioxidant Activity of Korean Rice Cake Added Cicer arietinum for Post-Menopausal Women - Park, Gun Hee; Ju, Hyun-Mok; Park, Yoon Jung; Lee, Eun Hye; Kim, Han Sol; Ma, Ri Na; Kim, Hyun Hee; Kim, Hyo Bin; Seo, Dong Jun; Min, Hae Rin; Kang, Gug In; Kim, Da Young; et al. (Pakistan Journal of Nutrition, 2015)
The symptoms caused by a decrease in hormone levels in women are referred to as menopause. These affect loss of femininity, cause estrogen-dependent disease and often develop into a personal as well as social issue. Menopausal women try to alleviate their symptoms by hormone injections and intake of functional health foods; however, many homemakers do not respond positively. Many soybean products include phytoestrogen similar to estrogen and Cicer arietinum also include phytoestrogen. For this reason, this study examined antioxidant activity of rice cakes supplemented with C. arietinum. The results were confirmed that antioxidant activity increased rice cakes supplemented with C. arietinum than normal rice cake. Above all, antioxidant activity was not decreased in cooking process. In these results mean that antioxidant activity of lignin as phytoestrogen in rice cake will not decrease. We introduce the potential of functional Korean rice cake that effective for ameliorating the symptoms of menopause.